IMPROVING THE STUDENTS’ PRONUNCIATION ABILITY THROUGH DRILLING TECHNIQUE - Ade Tika (Universitas Negeri Islam Sumatera Utara, 2022)
The study was aimed to describe the process and the results of the implementation of drilling technique as well as to improve the students’ pronunciation ability. The subjects of this study were 24 students of the seventh grade of MTs Alhikmah Darussalam. The method of this research was classroom active research (CAR) that employed Kemmis and Mc Taggar’s model consisted of 2 cycles. This study used both quantitative and qualitative data. Quantitatively, the data was collected by giving pre-test and post-test. It showed that the mean of students’ score in pre-test was 44,54 which only 20,8% or 5 from 24 students who passed the minimum passing grade (MPG). In the cycle I there were 9 or 37,5% who improved and the mean score was 58,79. Meanwhile In the cycle II, the students’ mean score was 78,125 which indicated that 18 students or 75% passed the MPG. Qualitatively, the data were collected through observation and interview. The result showed that there was improvement on student’s pronunciation achievement in each cycle which means that drilling technique could improve the students’ Pronunciation and the students were motivated, interested and enthusiastic in learning pronunciation. Keywords: Drilling, Technique, Pronunciation ability